Managing Business in a Muslim Majority Country: A Case Study of Boycott Factors in Non-Muslim Families in Indonesia (Ekonomi Syariah IAIN Kudus, 2025)
Business management in each country varied from one another based on their own characteristics, especially in Muslim-majority countries. The prolonged conflict between Israel and Palestine has led all countries to boycott Israeli products, whose movement is known globally as BDS (Boycott, Divestment, Sanctions). This quantitative study aims to determine the role of internal factors such as religiosity, self-enrichment, and ethnocentrism in influencing the intention to boycott Israeli-affiliated products. This study examines the willingness of non-Muslims in Indonesia to boycott Israeli-affiliated products. Four hundred respondents from 29 provinces in Indonesia and various backgrounds participated in this study. The analysis used structural equation modelling with partial least squares (SEM-PLS). The results showed that two factors positively influence boycott intentions: self-enhancement and ethnocentrism. Meanwhile, religious religiosity does not influence boycott intentions. The results of this study provide insights for international companies to provide complete transparency on their business operation related to humanistic and inclusive business practices if they want to be accepted by the Indonesian people.